Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-26T17:59:42+01:00
A) 5 (x-1) + 2x = 2 (x+2) + 6
5x-5+2x=2x+4+6
5x+2x-2x=4+6+5
5x=15/5
x=3

b) x + 4 - 5 (x-8)=x-6
x+4-5x+40=x-6
x-5x-x=-6-4-40
-5x=-50/5
x=-10

c) 6x - (x-1) = 6
6x-x+1=6
5x=5/5
x=1
2010-01-26T18:00:34+01:00
A)5x-5+2x=2x+4+6
5x+2x+2x=4+6-5
9x=5/:9
x=0,55...
b)x+4-5x-40=x-6
3x=-38
x=12,66...
c)6x²-6x=6
x²=6
2010-01-26T18:01:15+01:00
5 (x-1) + 2x = 2 (x+2) + 6
5x-5+ 2x = 2x+ 4+6
7x-5=2x+10
7x=2x+15
5x=15 II: 5
x=3


x + 4 - 5 (x-8)=x-6
x+ 4 -5x + 40 = x-6
-4x+44=x-6
44=5x-6
50=5x II : 5
x=10


6x - (x-1) = 6
6x-x + 1= 6
5x=5
x=1